2015
DOI: 10.1094/phyto-12-14-0367-fi
|View full text |Cite
|
Sign up to set email alerts
|

Maize Lethal Necrosis (MLN), an Emerging Threat to Maize-Based Food Security in Sub-Saharan Africa

Abstract: In sub-Saharan Africa, maize is a staple food and key determinant of food security for smallholder farming communities. Pest and disease outbreaks are key constraints to maize productivity. In September 2011, a serious disease outbreak, later diagnosed as maize lethal necrosis (MLN), was reported on maize in Kenya. The disease has since been confirmed in Rwanda and the Democratic Republic of Congo, and similar symptoms have been reported in Tanzania, Uganda, South Sudan, and Ethiopia. In 2012, yield losses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
215
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(229 citation statements)
references
References 42 publications
12
215
1
1
Order By: Relevance
“…Results from DAS-ELISA assay of samples from reift valley regions of Ethiopia showed that samples; collected from Zeway, Melkassa and Hwassa, showed very strong reaction to MCMV and SCMV which is in line with the report of (Mahuku et al 2015a, b).…”
supporting
confidence: 84%
“…Results from DAS-ELISA assay of samples from reift valley regions of Ethiopia showed that samples; collected from Zeway, Melkassa and Hwassa, showed very strong reaction to MCMV and SCMV which is in line with the report of (Mahuku et al 2015a, b).…”
supporting
confidence: 84%
“…Furthermore, MLN disease rating can be used for discarding susceptible germplasm at early screening stages before tolerant materials go into expensive multi-location testcross trials. Visual rating of MLN has been effective and efficient for screening large numbers of entries (Semagn et al 2015;Mahuku et al 2015). CIMMYT and its partners used visual screening as a preliminary step leading to the eventual release of four MLN tolerant hybrids for commercial production in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Average maize yield in SSA is 1.8 t/ha, which is significantly lower than other maize-growing regions in the developing world. Although several factors including low soil nitrogen, drought, foliar diseases, insect-pests and socio-economic factors contribute to low productivity, recently Maize lethal necrosis (MLN) disease has been one of the major factors affecting maize production in eastern Africa (Mahuku et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of maize has been limited by several diseases which cause serious grain loss (Anjichi, 2005;Pechanova, 2015). Recently, East Africa has been hit by another deadly disease called Maize Lethal Necrosis (MLN) which was not there before while potyviruses that form one of the causing pathogens used to exist (Wangai et al, 2012a;Wangai et al, 2012b;Adams et al, 2014;Gowda et al, 2015;Mahuku et al, 2015). The disease is caused by a combination of Maize Chlorotic Mottle Virus (MCMV) and other Potyviruses such as Sugar cane Mosaic Virus (SCMV), Maize Dwarf Mosaic Virus or Wheat Streak Mosaic Virus (Scheets, 1998;De Groote et al, 2016;Isabirye and Rwomushana, 2016).…”
mentioning
confidence: 99%